Re-Extension of 200 MW Turbine Cast Casing Service - Chernousenko, O.Yu.; Ryndyuk, D.V.; Peshko, V.A. (Проблеми машинобудування, 2019)
This paper assesses the residual life of casings on the basis of three-dimensional models of the K-200-130-3 steam turbine high-pressure (HP) and intermediate- pressure (IP) cylinder casings. In doing so, the paper takes into account the actual operating conditions according to the damage data obtained from the results of inspecting the power equip-ment metal condition during preventive maintenance overhauls. У роботі проведена оцінка залишкового ресурсу на базі тривимірних моделей корпусів циліндрів високого (ЦВТ) і середнього тиску (ЦСТ) парової турбіни К-200-130-3 з урахуванням реальних умов експлуатації згідно з даними пошкодження, отриманими за результатами обстеження стану металу енергетичного устаткування в планово-попереджувальних ремонтах. В работе проведена оценка остаточного ресурса на базе трехмерных моделей корпусов цилиндров высокого (ЦВД) и среднего давления (ЦСД) паровой турбины К-200-130-3 с учетом реальных условий эксплуатации согласно данным поврежденности, полученным по результатам обследования состояния металла энергетического оборудования в планово-предупредительных ремонтах.